Effectiveness of Guidance and Counselling Programme in Reducing Ethical Decline among Secondary School Students During Times of Socio-Economic and Political Challenges in Kwara State - Michael, Ifeoluwa; Abisoye, Faysol (citeus, 2025)
This study examined the effectiveness of guidance and counselling programs in reducing ethical decline among secondary school students during periods of socio-economic and political challenges in Kwara State. Four research questions guided the study, along with one hypothesis. Using a descriptive survey design, data were collected from a population of 3,780 Senior Secondary Three (SS3) students in Kwara State. A sample of 300 students, selected through stratified random sampling from six secondary schools, participated in the study. A self-developed structured questionnaire titled